Research in progress - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
COTA (Collectif d exchanges pour la technologie appropriee/appropriate technology exchange group) has begun a study, commissioned and funded by the EEC, on the techniques necessary for the identification, follow-up, and evaluation of small...